Age Limit for Regional Head Candidates: A Comparative Study of Administrative Law and Its Implications for Regional Leadership - Arifin, Firdaus (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The age limit for local government leaders is a crucial aspect of administrative law systems that impacts the effectiveness and quality of local leadership. This study aims to explore the effects of age limits on local leadership through a comparative analysis of Germany, the United States, and Sweden. The research employs a comparative legal approach and document analysis to assess how age limits influence effectiveness and diversity in local leadership. The findings indicate that strict age limits, as in Germany, support stability but constrain innovation, while flexible age limits in the United States enhance inclusivity but may reduce quality. The moderate approach in Sweden effectively balances experience with innovation. The study suggests the need for a balanced age limit policy to improve the effectiveness of local leadership and accommodate candidate diversity. This research concludes that policy adjustments and regular evaluations can optimize age limit policies in the context of regional government.